The Role of Midlatitude Cyclones in the Emission, Transport, Production, and Removal of Aerosols in the Northern Hemisphere. Issue 6 (27th March 2023) - Robinson, Joseph; Jaeglé, Lyatt; Oman, Luke D.
Abstract: We examine the distribution of aerosol optical depth (AOD) across 27, 707 northern hemisphere (NH) midlatitude cyclones for 2005–2018 using retrievals from the Moderate Resolution Spectroradiometer (MODIS) sensor on the Aqua satellite. Cyclone‐centered composites show AOD enhancements of 20%–45% relative to background conditions in the warm conveyor belt (WCB) airstream. Fine mode AOD accounts for 68% of this enhancement annually. Relative to background conditions, coarse mode AOD is enhanced by more than a factor of two near the center of the composite cyclone, co‐located with high surface wind speeds. Within the WCB, MODIS AOD maximizes in spring, with a secondary maximum in summer. Cyclone‐centered composites of AOD from the Modern Era Retrospective analysis for Research and Applications, version 2 Global Modeling Initiative (M2GMI) simulation reproduce the magnitude and seasonality of the MODIS AOD composites and enhancements. M2GMI simulations show that the AOD enhancement in the WCB is dominated by sulfate (37%) and organic aerosol (25%), with dust and sea salt each accounting for 15%. MODIS and M2GMI AOD are 60% larger in North Pacific WCBs compared to North Atlantic WCBs and show a strong relationship with anthropogenic pollution. We infer that NH midlatitude cyclones account for 355 Tg yr −1 of sea salt aerosol emissions annually, or 60% of the 30–80°N total. We find that deposition within WCBs is responsible for up to 35% of the total aerosol deposition over the NH ocean basins. Furthermore, the cloudy environment of WCBs leads to efficient secondary sulfate production. Plain Language Summary: Large‐scale storms occur during all seasons in the northern hemisphere (NH) midlatitudes and are responsible for a significant fraction of observed midlatitude precipitation. The meteorological environment of these cyclones influences the direct emission, removal, chemistry, and transport of aerosols. This study combines satellite observations and a global computer simulation to probe each of these processes. To do so, cyclone‐centered composites are generated by averaging together 27, 707 individual NH cyclone cases between 2005 and 2018. Results show that the total column amount of aerosol within the rain‐producing part of cyclones is enhanced and that most of this enhancement is in the form of smaller aerosol particles more likely associated with human activities. Cyclone region and season play a large role in the abundance of aerosol, with springtime cyclones downwind of Asia displaying the largest abundances. We find that strong winds within cyclones account for over half of the annual direct emission of sea salt aerosol over the NH oceans. Furthermore, we show that midlatitude cyclones efficiently remove aerosol, accounting for 27%–33% of the total over the NH ocean basins. They also account for 27% of secondary production of sulfate and facilitate aerosol transport. Key Points: Satellite observations show 20%–45% enhancement of aerosol optical depth in the warm conveyor belt airstream of midlatitude cyclones A global model attributes 37% of these enhancements to sulfate, 25% to organic carbon, 15% to dust, and 15% to sea salt aerosol (SSA) Midlatitude cyclones lead to 355 Tg yr −1 of SSA emissions, or 60% of the total over the northern hemisphere oceans